Social responsibilities of Islamic banks case study of bank Islam Malaysia Bhd & Bank Muamalat Malaysia Bhd - Musa, Muhammad Adli (2016)
It is claimed that the difference between Islamic and conventional finance is that the former has to preserve certain social objectives, while the latter need not be concerned with the moral implications of their business ventures. The Islamic Financial Services Board (IFSB) suggests that sharīʿah compliance is manifested in the ability of Islamic financial institutions (IFIs) not only to demonstrate that their operations are governed by an effective system of sharīʿah governance but also that they conduct their activities in a socially responsible manner. This paper seeks to establish the social responsibilities of IFIs and explore the extent to which two full-fledged Malaysian Islamic banks, Bank Islam Malaysia Bhd (BIMB) and Bank Muamalat Malaysia Bhd (BMMB), translate their social responsibility commitments into practice. This is achieved by analysing their annual reports and annual financial statements for a period of six years (2010-2015). Generally, the banks are committed to playing a social role by providing support to various organisations that provide benefits to society and by participating in government socially-oriented activities. Nonetheless, the percentage of financing provided for sectors deemed beneficial for society is relatively small and the portion of financing provided to small and medium enterprises generally declined over the years.